Analysis of Marine Ecotourism Suitability Based on Physical Environmental Conditions and Water Quality Index at Arta Sungai Limau Beach, Padang Pariaman Regency - Livi, Aldisa Sipti; Mubarak, Mubarak; Yoswaty, Dessy (Journal of Coastal and Ocean Sciences, 2024)
Marine ecotourism is a type of tourism that involves activities related to marine activities carried out under or above the sea surface. Marine ecotourism generally covers three areas: the sea surface, under the sea, and on the coast. Marine ecotourism activities, especially beach tourism, are highly dependent on the condition of the oceanographic parameters of the region for the safety and comfort of tourists. This research was conducted in Arta Beach, Padang Pariaman Regency, West Sumatra Province, to determine the suitability of marine ecotourism at Arta Beach based on the parameters of physical environmental conditions. This study used a survey method: observation and data collection at the research location. Data analysis is used for the Tourism Suitability Index (IKW) method for physical environmental parameters and the STORET method for water quality parameters. The results of this study indicate that the tourism suitability index based on the physical condition of the environment carried out at Arta Beach at station 1 received a value of 2.49, including the suitable category, at station 2 received a value of 2.5, including the suitable category and station 3 received a value of 2.49 including the suitable category. The overall average value of IKW on Arta Beach is 2.49, included in the suitable category. This value means this beach can be used for beach ecotourism. Water quality parameters are analyzed using the storey method. The data obtained from the pH, DO salinity, and temperature parameters meet the quality requirements (good condition) and are suitable for marine tourism activities